Analysis of Departure Waiting Room Terminal Capacity on Passenger Volume at Patimura Ambon International Airport, Maluku Province - Elfira Maya Dewi Masbait; Walid Jumlad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Departure terminal capacity to passenger volume at Patimura Ambon International Airport, Maluku Province in 2021 has experienced an increase in the number of passengers, won the Airport Service Quality (ASQ) award, in the airport category with a capacity of less than 2 million per year, from this statement the researcher wants to conduct a wide capacity analysis waiting room terminal, seating facilities, and passenger volume, whether the research results need development or not. The data in this study used secondary data, namely data on the number of passengers in the last three years, and primary data, namely data on the number of existing passenger departure terminal seats. Data analysis used descriptive statistical methods based on the formula in SKEP/347/XII/99, Director General of Civil Aviation. The results of the study stated that the area of the departure waiting room was 220 mÂ² based on SKEP 77/VI/2005 Director General of Civil Aviation. The capacity of the departure waiting room at Gate-1 to gate-5, gates 1 and 2 can accommodate passengers, gate-3 = 271 passengers, gate-4 = 267 passengers and gate-5 = 247 passengers. The need for seats based on SKEP 77/VI/2005 Director General of Civil Aviation is 828 seats. The results of the analysis of the capacity of the Departure Waiting Room Terminal for Passenger Volume at Patimura Ambon International Airport, Maluku Province, were declared to be appropriate based on SKEP 77/VI/205 of the Director General of Civil Aviation.